Pain Score in Adjustable Strabismus Surgery: Doi: 10.36351/pjo.v36i2.912 - Nadeem, Sana (Pakistan Journal of Ophthalmology, 2020)
Purpose: To assess the pain experienced by patients at the time of suture adjustment using topical proparacaine hydrochloride 0.5% anesthesia, in adjustable suture strabismus surgery. Study Design: Prospective, interventional study. Place and Duration of Study: Eye department of Fauji Foundation Hospital, Rawalpindi from May, 2017 to March, 2019. Material and Methods: A prospective study was carried out to assess the pain experience of patients undergoing suture adjustment under topical proparacaine hydrochloride 0.5% anesthesia, during routine adjustable squint surgery. All surgeries were performed under general anesthesia with suture adjustment done 1 hour or more after surgery when the effects of general anesthesia had worn off. Horizontal and vertical muscle recessions and resections were included along with inferior oblique surgeries, and transposition procedures. The patients were given the ‘Wong-Baker FACES® Pain rating Scale’; along with a ‘Numeric Pain Rating Scale’ from 0 to 10 (0 signifying ‘no pain’ and 10 signifying ‘worst possible pain’) on a proforma. The response of the patients was noted. Results: Thirty three patients who underwent adjustable strabismus surgery were included in this study. The mean age was 19.1 ± 11.1 years. The average number of muscles operated upon for each patient were 2.87 ± 1.08. The patients’ response to the ‘Wong-Baker FACES® Pain rating Scale’ ranged from 0 to 8, with a mean of 2.03 ± 1.81 SD. On the ‘Numeric Pain Rating Scale’ a similar response was obtained with a mean of 2.0 ± 1.82 SD. Augmentation of anesthesia was not needed in any patient. Conclusion: Adjustment of sutures under topical proparacaine hydrochloride 0.5% anesthesia after strabismus surgery is a practical, comfortable and safe procedure.